CORONARY HEART DISEASE. ANGINA TREATMENT - Ergashov Bekhruzjon Komilovich (Journal of new century innovations, 2024)
The causes, principles of diagnosis, prevention and treatment of coronary heart disease (CHD) and angina pectoris are outlined. The main components of nursing care for ischemic heart disease and angina pectoris are presented.